THOLPAVAKOOTHU:A STUDY ON THE PERFORMING ART OF SHADOW PUPPETRY IN KERALA - Nishanth, Anisha (International Journal of Research -GRANTHAALAYAH, 2021)
Tholpavakoothu is a form of shadow puppetry which is the ancient art form found only in Kerala and it is a ritualistic worship for Goddess Devi. The main theme of tholpavakoothu is based on Kamba Ramayan and puppets which are chiseled out beautifully on the animal skin are used for the puppetry. Unlike other puppetry, it is the black shadow of puppets that forms on the white screen in the presence of oil lamps that portrays the tale of Ramayana. The study is for the deeper understanding of the origin, style, forms, and themes of tholpavakoothu and also to find out the different influences of applied puppetry in tholpvakoothu. This study uses a qualitative approach using interviews with the artists and performances. It has given a deeper understanding of the uniqueness of tholpavakoothu compared to other puppetry forms. This form basically emphasizes the concepts of mythology and how the form has taken a transition to contemporary issues to cater to all types of audiences.